Anomalous rejection ratios in nanofiltration experiments. - Jason Dennis Shirley (2008)
Nanofiltration by its nature is used to concentrate material. It has been found that varying the solute feed concentration had an effect on the rejection of amino acids and polar molecules. The rejection of these organic solutes has been shown to increase with concentration during nanofitration experiments for a NTR 7450 membrane. The rejection of glycine increased from 29.4% to 72.2% for a concentration of 0.004 g/1 and 4.0 g/1 respectively. Similar increases in rejection with respect to concentration were observed for glutamine and glutamic acid, as well as for glucose, sucrose and raffinose over the same concentration range. The reliability of the filtration measurements was established by error analysis and the associated error for the glycine rejection was found to be +/- 3%. Therefore, the observed rejection increase could not be attributed to experimental error. This phenomenon was further investigated by particle size analysis and osmotic pressure measurement. The results from these experiments indicated that dimerisation was not occurring, thus no association between increasing molecular weight and solute concentration. The properties of the NTR 7450 membrane were investigated by streaming potential measurements, titrations and molecular weight cut-off experiments. The molecular weight cut-off of the membrane was found to reduce for an increase in solute concentration. This result implied that the effective pore size changed as a function of concentration and was attributed to adsorption occurring on the inner pore wall. The level of adsorption was further investigated by applying the Freundlich adsorption isotherm to measured permeated flux decline for increasing solute concentration. This method was adapted to enable analysis of the effect of adsorption on rejection with concentration.